2017
DOI: 10.1159/000455964
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Nitrergic Neuronal System Organization in the Brain of Two Holostean Fishes (Actinopterygii: Ginglymodi)

Abstract: The study of the nitrergic system, formed by the networks of neurons containing the enzyme nitric oxide synthase (NOS), has been extremely useful in unraveling neuroanatomical features of the organization of the central nervous system of vertebrates. Thus, data are available for representatives of most vertebrate classes and, in particular, several studies have detailed the organization of this system in teleosts. In contrast, no information is available regarding this neurotransmission system in the brains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 280 publications
(437 reference statements)
12
41
0
1
Order By: Relevance
“…Antibody specificity against neuronal NOS was assessed by liquid‐phase adsorption experiments (Simonian & Herbison, ). In addition, the specificity of the antiserum for detection of NOS was warranted by the observation of a staining pattern that was identical to that in previous reports in which it matched the NADPH diaphorase histochemical reaction (Brüning & Mayer, ; González et al, ; López et al, ; López & González, ; López, Lozano, Morales, & González, ; Moreno & González, , ; Moreno, López, Sánchez‐Camacho, & González, ; Muñoz, Marín, & González, ; Smeets et al, ). The immunoreactivity is abolished by absorption of the K205 antiserum with recombinant neuronal NOS protein (1 mM overnight at 4°C).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Antibody specificity against neuronal NOS was assessed by liquid‐phase adsorption experiments (Simonian & Herbison, ). In addition, the specificity of the antiserum for detection of NOS was warranted by the observation of a staining pattern that was identical to that in previous reports in which it matched the NADPH diaphorase histochemical reaction (Brüning & Mayer, ; González et al, ; López et al, ; López & González, ; López, Lozano, Morales, & González, ; Moreno & González, , ; Moreno, López, Sánchez‐Camacho, & González, ; Muñoz, Marín, & González, ; Smeets et al, ). The immunoreactivity is abolished by absorption of the K205 antiserum with recombinant neuronal NOS protein (1 mM overnight at 4°C).…”
Section: Methodssupporting
confidence: 67%
“…Alternatively, immunohistochemical detection of NOS directly reveals the nitrergic structures, although some mismatches between the two methodological approaches have been reported (Kharazia, Schmidt, & Weinberg, ; Sobreviela & Mufson, ; Vizzard, Erdman, Roppolo, Forstermann, & de Groat, ). Thus, the anatomy of the nitrergic system has been extensively studied by histochemical and immunohistochemical methods in the brain of most groups of vertebrates (for references see Alonso et al, ; López, Lozano, Morona, & González, ; López, Lozano, Morales, & González, ). In particular, several studies have described the organization of the nitrergic system in ray‐finned fishes, primarily teleosts (Anken & Rahmann, ; Arévalo et al, ; Bell, Pereda, & Faber, ; Brüning, Katzbach, & Mayer, ; Giráldez‐Pérez, Gaytan, & Pasaro, ; Giráldez‐Pérez, Gaytan, Ruano, Torres, & Pasaro, ; Holmqvist et al, ; Holmqvist, Ostholm, Alm, & Ekstrom, ; Singru, Sakharkar, & Subhedar, ; Villani & Guarnieri, ; Virgili, Poli, Beraudi, Giuliani, & Villani, ).…”
Section: Introductionmentioning
confidence: 99%
“…After rinsing 3 times in PB, the sections were mounted on glass slides and coverslipped with UltraCruz TM mounting medium containing DAPI for fluorescence labeling of DNA (Santa Cruz Biotechnology, sc-24941). The specificity of the TH and 5-HT antisera has been previously described [Morona et al, 2013;González et al, 2014;López et al, 2017], and the pattern of staining observed for NPY was consistent with that reported for L. ocu latus [Chiba, 2005].…”
Section: Double Orexin and Npy Th Or 5ht Immunolabelingsupporting
confidence: 85%
“…The nomenclature is the same used in our previous studies on holosteans [Morona et al, 2013;López et al, 2017], and essentially follows previously used terms in these species [Northcutt, 1982;Parent and Northcutt, 1982;Northcutt, 1991a, 1991b;Butler and Northcutt, 1992;Northcutt and Butler, 1993;Heijdra and Nieuwenhuys, 1994;Collin and Northcutt, 1995;Meek and Nieuwenhuys, 1998;Chiba and Oka, 1999;Baker and Bird, 2002;Chiba, 2005], but incorporates the terminology of the prosomeric model for the forebrain Rubenstein, 2003, 2015].…”
Section: Evaluation and Presentation Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation